Why Do Firms Recruit Internationally? - Rainer Winkelmann (Institute for the Study of Labor (IZA), 2001)
The paper studies the demand for foreign graduates at the firm level. Using a unique dataset on recruitment policies of firms in four European countries, the determinants of demand for internationally mobile high-skilled employees are established. I investigate the number, origin, skills, and functions of foreign graduates, as well as the experiences of firms recruiting internationally. A number of hypotheses for the international demand are formulated and assessed. Foreign highly-skilled employees are recruited mainly because of their special skills, be it international competence or technical know-how, that are not available domestically.
Keywords: L20; F22; J61; 330; Foreign graduates; labor shortage; transfer of knowledge; Arbeitsnachfrage; international; Hochqualifizierte Arbeitskräfte; Ausländische Arbeitskräfte; Wissenstransfer; Schätzung; Deutschland; Frankreich; Großbritannien; Niederlande